Hepatitis B virus genotypes A and D in Uganda - Zirabamuzale, Jackie T.; Opio, Christopher K.; Bwanga, Freddie; Seremba, Emmanuel; Apica, Betty S.; Colebunders, Robert; Ocama, Ponsiano (Journal of virus eradication, 2016)
The prevalence of hepatitis B virus (HBV) infection in Uganda is 10%. Hepatitis B virus genotypes impact on treatment response, rate of spontaneous recovery and progression of chronic HBV infection and hepatocellular carcinoma. There is little information on the HBV genotypic distribution in Uganda. Objectives: To determine HBV genotypes in Uganda. Methods: The MBN clinical laboratory performs HBV viral load and genotype testing in Uganda. It receives hepatitis B surface antigen (HBsAg)-positive samples from all over the country for additional HBV testing. Samples are stored for 6 months before being discarded. Our study used delinked stored samples. PCR-positive samples had DNA extracted and used as template for HBV genome amplification by nested PCR. Reverse hybridisation was performed and genotypes were determined by the line probe assay method (INNO-LiPA). Results: One hundred stored HBsAg-positive plasma samples with detectable viral loads were analysed. Of these, 93 samples showed PCR amplification products and gave genotype-specific probe lines on the INNO-LiPA assay. Of the patients, where gender was recorded, 60.9% were female, and the overall median age (IQR) was 25 (2–60) years. There was a predominance of HBV genotype D (47 patients; 50.5%), followed by genotype A, (16 patients; 17.2%). One patient (1.1%) had genotype E. In 28% of the samples mixed infections were detected with genotypes A/E (9.7%) and A/D (6.5%) being most common. Genotypes B, C, E and H only occurred as part of mixed infections. Conclusion Hepatitis B genotypes D and A were predominant in our study population.
Keywords: Hepatitis B virus genotypes; Uganda